Política e sociedade nas estradas transversais da América Latina : o neoliberalismo e o posiberalismo? (1980-2014) - Dos Santos Sousa, Andreza (Revista de Casos e Consultoria.)
Understanding the problems of social movements in Latin America, the work of the left or center-left, the emergence of multilateral organizations, and their influence in Latin American countries are important to understand a little more about the current historical, economic and social context, as well as the policies were designed in these countries. It is a complex scenario, marked by strong changes, where the facts occur simultaneously. Neoliberalism arises in order to reduce the role of the state, but this accentuates social inequalities, raises unemployment rates, increases the criminalization of social protest, and dictates what each country should specialize in the name of a so-called structural reform . The social struggles were intense and the left comes to power, but undergoes changes in some countries takes a center-left stance, but that is not everything, because the multilateral organizations despite giving in to the pressures of social movements, within the scope of social policies they still interfere with other policies as we can verify in the case of Brazil with the Basic Education Program for the North and Central West Regions (Monhangara Program), which was one of the projects financed by the World Bank. These are some elements that are present at the crossroads of Latin America living a post-liberal policy.